Internet telephony services for presence with SIP and extended CPL - Jiang, Dongmei (University of Ottawa (Canada), 2004)
Internet Telephony is the next generation of telephony with many new features and low cost. Because of the explosion of new features, it has become critical to control and manage these features. The main challenge in Internet Telephony is service programming. The Call Processing Language (CPL) is a solution for end users to describe and control their services in Internet Telephony. Current CPL focuses on call processing services only. It is not adequate for the definition of many types of new services, such as the combination of telephony services with email, instant messaging, presence etc. This thesis extends CPL to describe new Internet Telephony services including presence services and call processing services related to presence. In the thesis, the presence system is systematically described in a three-layer architecture. End user's presence services and system basic services are clearly separated in the architecture. Presence information, as the basis of presence services, is extended from traditional "online" and "offline" indicators to include broader meaning, such as location, phone line status, role and availability status etc. Through CPL extensions for presence, user's new presence services and new presence related call processing services are illustrated by using various examples. A simulation system is implemented to demonstrate the Internet Telephony services specified in extended CPL. End users can create and modify their own services via the Graphic User Interfaces (GUIs) and access their services at any location through the Internet. The simulation system is verified with various test cases.
Keywords: Computer Science.